A Systematic Review of the Probability of Repeated Admission Score in Community‐Dwelling Adults. Issue 3 (15th March 2013) - Wallace, Emma; Hinchey, Tim; Dimitrov, Borislav D.; Bennett, Kathleen; Fahey, Tom; Smith, Susan M.
<x xml:space="preserve">Abstract</x> Objectives To perform a systematic review of the Probability of Repeated Admission (Pra) score in community‐dwelling adults to assess its performance in a range of validation studies in the community setting. Design Systematic review and meta‐analysis. Setting Primary and community care. Participants Community‐dwelling older people. Measurements The primary outcome was hospital admission; secondary outcomes were mortality, hospital days, functional decline, other health service use, and costs. Results Nine validation studies describing 11 cohorts of individuals aged 65 and older were identified. A meta‐analysis of the Pra score in five cohorts (8, 843 individuals) with comparable and available data revealed good discrimination performance (summary area under the receiver operating characteristic curve 69.7% (standard error 2.8%)). Pooled specificity was high (96%, 95% confidence interval (CI)=95.8–96.7%), indicating that a Pra score of 0.5 or greater effectively rules in the likelihood of admission, but pooled sensitivity was low (12%, 95% CI=10.5–13.6%). Calibration performance was good, with an overall risk ratio of 1.12 (95% CI=0.89–1.42), indicating that the Pra score reliably predicted hospital admissions. Conclusion The Pra score performs well in predicting hospital admission in community‐dwelling adults categorized as high risk according to the score. This tool has clinical and healthcare policy utility in terms of targeting elderly people at highest risk of hospital admission, but the low pooled sensitivity of the score indicates that it is not a reliable way of excluding hospital admission in those stratified as low risk.